Side‐View Operando Optical Microscopy Analysis of a Graphite Anode to Study Its Kinetic Hysteresis. Issue 6 (5th March 2020) - Kang, Sujin; Yeom, Su Jeong; Lee, Hyun‐Wook
Abstract: Operando analyses have provided several breakthroughs in the construction of high‐performance materials and devices, including energy storage systems. However, despite the advances in electrode engineering, the formidable issues of lithium intercalation and deintercalation kinetics cannot be investigated by using planar observations. This study concerns side‐view operando observation by optical microscopy of a graphite anode based on its color changes during electrochemical lithiation. Since the graphite color varies according to the optical energy gap during lithiation and delithiation, this technique can be used to study the corresponding charge–discharge kinetics. In addition, the cell configuration uses liquid electrolytes similar to commercial cells, allowing practical application. Furthermore, this side‐view observation has shown that microscale spatial variations in rate and composition control the insertion and deinsertion, revealing the kinetics throughout the whole electrode. The results of this study could enhance the fundamental understanding of the kinetics of battery materials. Abstract : A certain point of view : Graphite color varies according to the optical energy gap during lithiation and delithiation, and this can be used to study the corresponding charge–discharge kinetics. Side‐view observation shows that microscale spatial variations in rate and composition control the insertion and deinsertion, revealing the kinetics throughout the whole electrode.